2023
DOI: 10.1002/aenm.202303629
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Toward Efficient and Durable Anion Exchange Membrane Water Electrolyzers Enabled By Electro‐Active Porous Transport Layers

Andrew W. Tricker,
Tugrul Y. Ertugrul,
Jason K. Lee
et al.

Abstract: Green hydrogen, produced via water electrolysis using renewable electricity, will play a crucial role in decarbonizing industrial and heavy‐duty transportation sectors. Anion exchange membrane water electrolyzers (AEMWEs) can overcome many of the performance and cost limitations of incumbent technologies, however, still suffer from durability challenges due to oxidative instability of anion‐exchange ionomers. Herein, the use of an electro‐active porous transport layer as anode (PTL‐electrode) is demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“… 49 In addition, X-ray photoelectron spectroscopy (XPS) of the EOL cathode catalyst layer shows severe loss of nitrogen from the cationic functional headgroup ( Figure S14 ). AEIs are more prone to oxidative decay under anodic potential; 50 however, degradation could also occur if exceeding the electrochemical stability window even under reductive potential. The performance metrics of this work is compared to that of previously reported BPM CO 2 electrolyzers for CO production ( Table S1 ), 29 , 31 , 51 which indicates enhanced efficiency and durability, although differences in the testing condition and the material should be noted.…”
Section: Resultsmentioning
confidence: 99%
“… 49 In addition, X-ray photoelectron spectroscopy (XPS) of the EOL cathode catalyst layer shows severe loss of nitrogen from the cationic functional headgroup ( Figure S14 ). AEIs are more prone to oxidative decay under anodic potential; 50 however, degradation could also occur if exceeding the electrochemical stability window even under reductive potential. The performance metrics of this work is compared to that of previously reported BPM CO 2 electrolyzers for CO production ( Table S1 ), 29 , 31 , 51 which indicates enhanced efficiency and durability, although differences in the testing condition and the material should be noted.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with the literature, where the crucial role of Fe in enhancing Ni and Co-based hydroxide activity is reported [ 44 , 45 , 46 ]. Moreover, a substrate of LDH-based electrocatalytic layer is SS, and it has been demonstrated that stainless steel can represent a good electrocatalyst for OER due to its capacity of forming active (oxy)hydroxides under oxidizing conditions [ 2 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zero-gap configuration leads to higher efficiency, and it foresees the usage of a so-called porous transport layer (PTL), which ensures electrical continuity between the catalytic layer and the current collector, and that is crucial to remove bubbles from the catalytic layer [ 10 , 11 ]. Functionalizing PTLs with a catalytic layer can be a way to further increase the cell efficiency [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study suggests that future research should focus on developing active and stable materials for catalysts, catalyst layers, and the integration of catalyst layers into MEAs, particularly as the anode components are highly susceptible to oxidative conditions. Also, more recent results by Peng et al 605 and Lee et al 606 demonstrated a relatively low degradation rate (5–50 μV h −1 ) of 1 M KOH-fed AEMWEs employing aryl ether-free AEMs at 1.5 and 2 A cm −2 , achieving a practical level of hydrogen generation.…”
Section: Device Performancementioning
confidence: 95%